Hot topics and frontier evolution of growth-mindset research: a bibliometric analysis using CiteSpace - Xu, Jianmei; Xu, Wenqiong (Frontiers in Psychology, 2024)
By virtue of Citespace, this study aimes to evaluate and pinpoint the status, hot areas, and frontiers of growth-mindset research. Co-authorship analysis, co-citation analysis, co-occurrence analysis, cluster analysis, and content analysis are conducted, based on 543 articles selected from the Social Sciences Citation Index database. Researchers from Australia and countries/territories in North America, East Asia, and Western Europe have maintained relatively closer cooperation with each other. Carol S. Dweck, Jeni L. Burnette, David S. Yeager, and Mary Murphy have high publication volumes and close connections with each other. Angela Duckworth has acted as a bridge among many researchers. Highly co-cited literature has mainly focused on the impacts of mindset and intervention measures. In the past two decades, the literature on mindset research has plunged into numerous hot topics in terms of implicit theory, intelligence, motivation, beliefs, achievements, academic performance, students, transitions, and psychological intervention. Based on burst detection, the field of growth-mindset research shows the following trends: (1) future research must pay more attention to fidelity in intervention studies, conduct rigorous manipulation tests at the statistical level, and improve causal relationship models between growth mindset and other variables and (2) use a multidisciplinary perspective to provide a deeper explanation of the formation mechanism of the growth mindset. Finally, (3) the function mechanisms of the growth mindset in different cultural backgrounds should be strengthened.